2012
DOI: 10.4329/wjr.v4.i8.378
|View full text |Cite
|
Sign up to set email alerts
|

Imaging investigation of pancreatic cystic lesions and proposal for therapeutic guidelines

Abstract: By using the proposed algorithm, cystic mucinous tumors of the pancreas were detected and proper operative interventions would have been rendered with fewer diagnostic examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…After title and abstract review, 1359 studies were eligible for full‐text review. Fifteen studies met the inclusion criteria, all of which were retrospective 18,19,27,33–44 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After title and abstract review, 1359 studies were eligible for full‐text review. Fifteen studies met the inclusion criteria, all of which were retrospective 18,19,27,33–44 …”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported on PCLs with a PDAC at the time of initial MRI (Table 1). 27,33–35,37–39,44 The median year of publication for the eight publications was 2017 (range, 2010–2022). All studies used single‐center databases from Italy ( N = 4), Bulgaria ( N = 1), Canada ( N = 1), Japan ( N = 1), and South Korea ( N = 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations